STRATEGI PEMASARAN INDIHOME MENGHADAPI PERSAINGAN DI MASA ADAPTASI COVID-19 - Ni Nyoman Sunariani; Ni Made Ayu Nila Kumala Sari (Media Bina Ilmiah, 2022)
Marketing strategy is the company's way to achieve marketing goals through the target market and marketing mix. The purpose of this study was to determine indiHome's marketing strategy in the face of competition during the COVID-19 adaptation period. The research method used is a qualitative approach, with the type of descriptive research, data collection analysis techniques are carried out with observation, interviews, and documentation techniques. Data analysis with marketing strategy analysis of segmentation, target, position and analyze through SWOT analysis. The results showed that PT. Telkom Indonesia, Tbk Bali Ubung Denpasar Branch in marketing using a more for less marketing strategy, carrying out complaint handling via video calls with technicians to ensure internet service remains excellent, The results of the SWOT matrix analysis and diagrams are in quadrant I, meaning that they have sufficient power to utilize opportunity, the most suitable new strategy to use is an aggressive growth strategy or a strength of opportunity strategy (SO Strategy) such as car branding. Findings, there are many complaints, especially from personal customers because the technicians cannot handle it quickly when the internet network is interrupted during the COVID-19 pandemic.